The dark triad personality in predicting intention towards infidelity among married couples in Malaysia - Cheah, Al Kaid; Chen, Hui Yi; Muhamad Sharfudin, Abdul Kader (2021)
Nowadays, the number of divorce cases has been continuously increasing in Malaysia. One of the main reasons is the infidelity issue in a romantic relationship. Thus, a quantitative, cross-sectional study was used to examine the predictive effect of the Dark Triad personality on intention towards infidelity among married couples in Malaysia. An online survey was distributed to 87 Malaysian married couples using a purposive sampling method. The instruments used in the survey questionnaires were Short Dark Triad (SD3), and the Intentions Towards Infidelity Scale (ITIS). The data collected was analysed on SPSS by using Multiple Linear Regression (MLR). The results suggested that psychopathy was the only element of Dark Triad personality traits that significantly predicts intention towards infidelity among married couples in Malaysia. The results of the study can serve as a reference for practitioners such as marital counsellors in dealing with marital issues among couples in Malaysia.